Designing a Psychological Empowerment Model for Chronic Pain Management: A Qualitative Study - Violet Alipour; Farah Naderi; Behnam Makvandi; Reza Pasha; Parviz Asgari (Shiraz University of Medical Sciences, 2021)
Background: Given the chronic pain management complexities, achieving a model for managing chronic pain psychological dimensions is very important. Hence, the current study aimed to design a psychological empowerment model in chronic pain management. Methods: This qualitative method was conducted using a grounded theory approach; the main method of data collection was semi-structured interviews and participant observation. The participants were 15 members of the treatment team and six patients with chronic pain, selected via theoretical and purposive sampling from 2018 to 2020. Data analysis was performed concurrently with data gathering based on Corbin and Strauss's proposed method. Data validity was confirmed via Lincoln and Guba's criteria. Results: The developed psychological empowerment model in chronic pain management consists of six constructs including  "pain reasoning", "vulnerability", "pain interactions", "ailment", "facing pain", and "self-empowerment". Among them "self-empowerment" was identified as the major concept or core category. The themes of pain reasoning and vulnerability were identified as the cause and background  , respectively, which affected the phenomenon of ailment.   In this regard, the themes pain interactions and facing pain were also recognized as the interferers and approaches which lead to self-empowerment like the consequences, if implemented properly. Conclusion: The developed model in this study, as a caring model, can be used for compensating the lack of attention to chronic pain psychological dimensions in chronic pain management. Its use in clinical settings requires further studies on testing the above model on patients with chronic pain.